Knee Pain and Quality of Life among the Elderly - Melati, Akilla Nathania; Nugraheni, Nuniek; Djuari, Lilik; Yulianti, Erikavitri; Romadhon, Pradana Zaky (Universitas Airlangga, 2024)
Introduction: The aging process can lead to knee pain in the elderly, which negatively impacts their quality of life by decreasing their physical functioning and potentially affecting their psychological well-being over time. This study aimed to determine the association between knee pain and the quality of life of the elderly. Methods: This analytical study involved elderly patients aged 60 years and over who presented with complaints of knee pain at the Geriatric Outpatient Clinic of Universitas Airlangga Hospital, Surabaya, Indonesia, from September 2022 to March 2023. The participants were selected by consecutive sampling until a total of 50 samples were collected using the interview method. The independent variable was knee pain, while the dependent variable was quality of life. The instruments used were the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) to measure knee pain and the Barthel Index for Activities of Daily Living (ADL) to assess the quality of life. The data were analyzed using Spearman's rho, with p<0.01 indicating a significant correlation. Results: The majority of the elderly were female (54%) and fell within the age group of 66–70 years. The most prevalent complaint was mild knee pain (52%). A total of 50% of the elderly had an independent quality of life. A strong correlation was found between the degree of knee pain and quality of life in the elderly (p=0.000). The correlation coefficient indicated an inverse relationship between the degree of knee pain and quality of life in the elderly. Conclusion: The findings suggest that the higher the pain degree suffered by the elderly, the lower their quality of life. Highlights: 1. This study evaluated the factors that influence the quality of life of elderly individuals with knee pain, an issue that has been relatively overlooked in Indonesia. 2. The results of this study will hopefully assist scholars and stakeholders, enabling them to optimize the quality of life for elderly individuals experiencing knee discomfort.